2019
DOI: 10.1021/acs.iecr.8b05334
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Advancement of Porous Biopolymer Scaffold: Tissue Engineering Application

Abstract: Tissue engineering is a derivative of biomedical engineering, which deals with the repair and regeneration of organs or their tissues. Cell-embedded porous polymeric scaffolds unveil proficiency in rectifying the mechanical trauma of skin, bone erosion, and neurodegenerative diseases like spinal cord injury. Archetypically, pristine cell-based biomaterial scaffolds are utilized; however, investigations over time have validated that incorporation of additives such as silver nanoparticles or bioactive glass augm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(98 citation statements)
references
References 270 publications
(390 reference statements)
2
95
0
1
Order By: Relevance
“…Anitha et al [ 254 ] reported a composite matrix containing crystalline rod-shaped core with uniform amorphous silica sheath (Si–n HA), which showed good biocompatibility, osteogenic differentiation, vascularization, and bone regeneration potential. Silicate containing hydroxyapatite stimulates cell viability of human mesenchymal stem cells for extended proliferation [ 255 ]. Zhou et al [ 256 ] synthesized PLGA–SBA15 composite membranes with different silica contents by electrospinning method; these membranes showed better osteogenic initiation then the pure PLGA membranes.…”
Section: Nanobiomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anitha et al [ 254 ] reported a composite matrix containing crystalline rod-shaped core with uniform amorphous silica sheath (Si–n HA), which showed good biocompatibility, osteogenic differentiation, vascularization, and bone regeneration potential. Silicate containing hydroxyapatite stimulates cell viability of human mesenchymal stem cells for extended proliferation [ 255 ]. Zhou et al [ 256 ] synthesized PLGA–SBA15 composite membranes with different silica contents by electrospinning method; these membranes showed better osteogenic initiation then the pure PLGA membranes.…”
Section: Nanobiomaterialsmentioning
confidence: 99%
“… Basic principle procedures for tissue engineering. (Adapted with permission from ©2019 American Chemical Society [ 255 ]). …”
Section: Figurementioning
confidence: 99%
“…Electrospinning is a promising and versatile technique that is used to fabricate polymeric nanofibers for a wide variety of biomedical applications such as drug delivery systems [1], scaffolds for tissue engineering [2] [3] [4] [5], wound dressing [6]. Fibers produced by electrospinning have controlled dimensions, about a few nanometers, and porosity, which give the produced fibers a high surface area [5] [7].…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is a promising and versatile technique that is used to fabricate polymeric nanofibers for a wide variety of biomedical applications such as drug delivery systems [1], scaffolds for tissue engineering [2] [3] [4] [5], wound dressing [6]. Fibers produced by electrospinning have controlled dimensions, about a few nanometers, and porosity, which give the produced fibers a high surface area [5] [7]. Achieving these characteristics depends on a wide range of factors such as solution parameters (polymer concentration, conductivity and viscosity), process-related parameters (polymer flow rate, distance tip-to-plate, and applied voltage), as well as humidity and temperature [1] [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation